Complete Sino Atrial Block in Acute Coronary Syndrome with ST Segment Elevation: Incidence, Predictive Factors and Related Mortality - ZOUZOU, Hanane (Clinical Medicine And Health Research Journal, 2023)
Background: Sino atrial block in acute coronary syndrome with ST segment elevation is not rare and may be dangerous by causing severe bradycardia. Its incidence was reported in the literature, but no data about its predictive factors or related mortality, also its epidemiological data is lacking in Algeria. Aims: The main objective of our study is the determination of the frequency of Sino Atrial Block in acute coronary syndrome with ST segment elevation, the secondary objective was the analysis of predictive factors of this Brady arrhythmia, and related mortality. Methods and materials: In this prospective study, conducted in the cardiology department of Hussein Dey hospital (Algiers-Algeria), 467 patients with acute coronary syndrome with elevated ST segment (87 women and 380 men) were enrolled between 28 February 2014 and 16 July 2015. The average age is 60 ± 13 years; at admission, a Holter recorder was attached for continuous ECG monitoring during 48 hours Kruskal’s ANNOVA or H tests were used for comparison of quantitative variables, χ2 test or Fisher’s exact test, were used for qualitative variables, all tests were performed with 1st species risk of 5%. Results: The frequency of complete Sino atrial block is 2.6 % (12 patients), CI 95%: [1.2%-4%], multivariate analysis identified the following independent predictors: right ventricular acute coronary syndrome, infero basal acute coronary syndrome, and large right atrium surface. The risk of mortality expressed by Hazard Ration (HR) is 5.4. (CI95%: [1.2-24], p = 0.024); right acute coronary syndrome is the only predictive factor of mortality identified in our study. Conclusion: Sino atrial block is not rare in acute coronary syndrome with elevated ST segment, its predictive factors according to our study are: right ventricular acute coronary syndrome, infero basal acute coronary syndrome, and large surface of right atrium, its occurrence increases the risk of hospital mortality.